Prevalence of a Hobnail Pattern in Papillary, Poorly Differentiated, and Anaplastic Thyroid Carcinoma: A Possible Manifestation of High-grade Transformation. (February 2015) - Amacher, Anne Marie; Goyal, Bella; Lewis, James S.; El-Mofty, Samir K.; Chernock, Rebecca D.
Abstract : Papillary thyroid carcinoma is the most common thyroid carcinoma and has a generally favorable prognosis. There are several well-characterized variants, some of which are associated with more aggressive clinical behavior. Hobnail is a recently described rare variant that appears to behave more aggressively. Initial reports characterizing this variant focused on primary tumors and excluded other recognized variants, as well as poorly differentiated and anaplastic thyroid carcinomas, from analysis. Here, we evaluate the frequency of hobnail features in both primary and metastatic papillary thyroid carcinomas, including in association with other known variants, and also in poorly differentiated and anaplastic thyroid carcinomas. Primary and metastatic papillary thyroid carcinomas from a 5-year period (2007 to 2011) and all available anaplastic and poorly differentiated thyroid carcinomas from a 22-year period (1989 to 2011) were retrieved from the files. Tumors from 478 papillary, 26 anaplastic, and 18 poorly differentiated thyroid carcinomas were reviewed for hobnail features present in >10% of each tumor. Hobnail features were most commonly observed in association with poorly differentiated thyroid carcinoma (4 of 18 cases, 22%) and were seen in only 1.3% of papillary thyroid carcinoma patients (6 of 478). One of 26 anaplastic carcinomas had hobnail features (3.8%). Among the papillary thyroid carcinomas, hobnail features were often associated with other histologic variants that are known to be more clinically aggressive, had increased mitotic activity, and/or necrosis and lymph node metastases at presentation. These findings suggest that hobnail features may be a manifestation of higher-grade transformation.